Cell Type Specific Suppression of Hyper-Recombination by Human RAD18 Is Linked to Proliferating Cell Nuclear Antigen K164 Ubiquitination - Colette B. Rogers; Wendy Leung; Ryan M. Baxley; Rachel E. Kram; Liangjun Wang; Joseph P. Buytendorp; Khoi Le; David A. Largaespada; Eric A. Hendrickson; Anja-Katrin Bielinsky (Biomolecules)
RAD18 is a conserved eukaryotic E3 ubiquitin ligase that promotes genome stability through multiple pathways. One of these is gap-filling DNA synthesis at active replication forks and in post-replicative DNA. RAD18 also regulates homologous recombination (HR) repair of DNA breaks; however, the current literature describing the contribution of RAD18 to HR in mammalian systems has not reached a consensus. To investigate this, we examined three independent RAD18-null human cell lines. Our analyses found that loss of RAD18 in HCT116, but neither hTERT RPE-1 nor DLD1 cell lines, resulted in elevated sister chromatid exchange, gene conversion, and gene targeting, i.e., HCT116 mutants were hyper-recombinogenic (hyper-rec). Interestingly, these phenotypes were linked to RAD18’s role in PCNA K164 ubiquitination, as HCT116 PCNAK164R/+ mutants were also hyper-rec, consistent with previous studies in rad18−/− and pcnaK164R avian DT40 cells. Importantly, the knockdown of UBC9 to prevent PCNA K164 SUMOylation did not affect hyper-recombination, strengthening the link between increased recombination and RAD18-catalyzed PCNA K164 ubiquitination, but not K164 SUMOylation. We propose that the hierarchy of post-replicative repair and HR, intrinsic to each cell type, dictates whether RAD18 is required for suppression of hyper-recombination and that this function is linked to PCNA K164 ubiquitination.